Pengenalan Pencatatan Keuangan Usaha Mikro Kecil dan Menegah Berbasis Digital di Kelurahan Situ Gede, Kecamatan Bogor Barat, Kota Bogor - Nia Kurniawati Hidayat; Gusti Raganata (Institut Pertanian Bogor, 2022)
Limitations of financial record system imply a difficulty for MSME actors in executing the right decisions in their business and accessing credit. This community service activity aims to provide awareness about the importance of financial records for MSMEs, an introduction to digital-based financial recording and financial recording practices for MSMEs. This training which is carried out offline and is attended by MSMEs in Situ Gede Village, West Bogor District, Bogor. This training begins with facilitating a participants’ discussion to gain an initial understanding of digital-based financial reports, then continues with the delivery of material and evaluation in the form of joint practice of making daily financial records of each participants’ businesses using digital application. Achievement on learning outcomes is measured by increasing participants’ skills in using digital financial recording applications (BukuWarung) to carry out financial records. The various features that exist in BukuWarung's digital financial records potentially support MSME actors to arrange their financial reports. Obstacles in implementing activities arise from the level of knowledge on basic accounting and proficiency in using digital technology. Around 80% of participants were able to make financial records using the application, while about 20% were unable to apply or partly due to application installation problems and unsupported devices. For the sustainability of the program, a dialogue platform that facilitates users exchange experiences and information regarding digital financial applications and continuous coaching is important to reduce obstacles that may occur in the future.